REAL AND FINANCIAL DETERMINANTS OF PENSION MARKETS - Barreto, Flávio Ataliba Flexa Daltro; Castelar, Luiz Ivan de Melo (Revista Econômica do Nordeste, 1999)
This paper analyses the real and financial determinants of private pension markets. A preliminary exam of a set of variables representing demand, the stock market and the financial market indicated that income per capita and volatility of the stok market are the main forces influencing pension market size. Regression analyses confirms formally this preliminary funding and shows that the former has a direct relation with pension market size whilst the later displays an inverse relation. Moreover, the elasticity of income per capita is about one third of the elasticity of volatility, implying that a steady growth of income combined with stability of the stok market is the perfect environment to the development of pension market.